Unusual Case of Pancreatic Adenocarcinoma with Bladder Metastasis - Arcovito, Giorgia (Medicina (Kaunas), 2020)
Background: The pancreas can be the site of neoplasms of several histogenetic origins; in most cases, tumors derive from the exocrine component, and ductal adenocarcinoma certainly prevails over the others. This tumor displays remarkably aggressive behavior, and it is often diagnosed at a late stage of disease. Case presentation: We discuss the rare case of a 76-year-old male with locally advanced pancreatic head adenocarcinoma who developed uncommon metastatic disease. The bladder constitutes a very rare site of metastases, mostly deriving from melanoma, gastric, lung and breast cancers. The bladder’s secondary involvement in pancreatic malignancies represents an extremely unusual occurrence, and there are very few cases described in the literature to date. Conclusions: The finding of pancreatic adenocarcinoma metastases leads to a poor prognosis, and patients who are diagnosed at this stage constitute 53% of cases, with a 5-year survival of 3%. Although rare, therefore, the diagnostic hypothesis of pancreatic ductal adenocarcinoma (DAC) metastases to the bladder must, in some cases, be considered, especially if accompanied by a clinical picture that may suggest it.